Molecular tracking of insulin resistance and inflammation development on visceral adipose tissue - Bensussen, Antonio; Torres-Magallanes, José Antonio; Roces de Álvarez-Buylla, Elena (Frontiers in Immunology, 2023)
Visceral adipose tissue (VAT) is one of the most important sources of pro-inflammatory molecules in obese people and it conditions the appearance of insulin resistance and diabetes. Thus, understanding the synergies between adipocytes and VAT-resident immune cells is essential to treat insulin resistance and diabetes. Using stochastic computational network models, we found that in lean people, insulin produces inflammation in adipocytes as a homeostatic mechanism to downregulate glucose intake. However, when the VAT tolerance to inflammation is exceeded, adipocytes lose insulin sensitivity according to severity of the inflammatory condition. Our results suggest that insulin resistance is initiated by inflammatory pathways and sustained by intracellular ceramide signaling. Our data show that insulin resistance potentiates the effector response of immune cells, which suggests its role as a nutrient redirection mechanism. Finally, we discuss the possible physiological role of this mechanism and its relationship with type 2 diabetes mellitus.